Transparency and collaboration at the heart of new developments at Crossref - Lammey, Rachael; Fairhurst, Vanessa (Septentrio Conference Series, 2018)
Watch the VIDEO. At Crossref we work to make research outputs easy to find, cite, link, and assess. If you’re really familiar with what Crossref does, then great! However, we’d love the opportunity to talk about some of the newer initiatives we’ve been working on. This involves ways to allocate identifiers to different types of research objects (preprints and peer reviews among others), and to connect those up to the related research. As well as new initiatives, we’re also making it easier for members to see a clear picture of the metadata that Crossref has. It can be hard for everyone at a publisher (or the wider community) to have clear idea of what metadata elements they’re depositing. We wanted to help show this, so that members can fill in metadata gaps and maximise the potential for their content to be discovered and reused by the thousands of tools and services who use Crossref. We’re also conscious that it can be difficult to provide all of this information to us, so we’re working on ways to help publishers provide the most complete metadata they can. We’ve involved members in all of the above initiatives, as advisors, advocates and beta-testers, and we’re also involved in projects that involve collaboration with wider communities. We invite you to share our love of metadata, think about how you can be involved and let us know what else you need - we welcome your input!